(untitled) (Revista de Ciências Agroveterinárias, 2014)
The gastrointestinal nematodiosis represents one of the main health problems of goats reared under grazing, and in Haemonchus contortus and Trichostrongylus colubriformis species it is the most responsible for economic losses of goat. The diagnosis of parasitic animal must be grounded in clinical evaluations and results of tests used, including the pasture. The degree of parasitic infection in animal and pasture contamination assist in the adoption of measures of grazing management (forage, height of grazing, pasture rotation and stocking rate) and anthelmintic treatment suitable for each system created in different geographic regions. This article was written according to the health and economic importance of gastrointestinal helminthiasis caused by nematodes in goats subjected to grazing.